FLAVONOID LEVEL ANALYSIS OF BINJAI LEAF EXTRACT (Mangifera caesia) IN ETHANOL, METHANOL, AND N-HEXANE SOLVENTS (Research report) - Didy Adham; Irham Taufiqurrahman; Zairin Noor Helmi (Dentino : Jurnal Kedokteran Gigi, 2019)
Background: Many wounds can manifest in various complaints such as pain, swelling and bruising. However, almost all of these wounds can be healed faster by utilizing herbal medicine. Binjai is one of herbal medicine originated from Mangifera genus and Anarcadiaceae family which roots and stems has been proven to contain secondary metabolites. Flavonoids are one of the metabolites which have the antioxidant, antibacterial and anti-inflammatory effect. This effect may contribute in the acceleration of wound healing process especially through flavanoid compound mechanism. Flavonoids themselves are found in the form of glycosides that are more soluble in polar solvents. Thus, they can be obtained by dissolving binjai leaves in methanol and ethanol solvents. Purpose: To determine differences of total flavonoid in binjai leaf extract using ethanol and methanol solvent. Methods: This type of research is a true experimental study with post-test only control group design. The samples was comprised of 27 repetitions consisting three groups, namely 70% ethanol treatment groups and 70% methanol  treatment groups. 70% n-hexane group was used as control. Results: There were significant differences between ethanol to methanol group at p = 0.000, ethanol with n-hexane group at p = 0.000 and between methanol with n-hexane group at p = 0.000. Conclusions: There were differences of total flavonoid in binjai leaf extract using ethanol and methanol solvent.